Quantitative assessment of the sensitivity of dormant AML cells to the BAD mimetics ABT-199 and ABT-737 - Yu, Ning; Seedhouse, Claire; Russell, Nigel; Pallis, Monica (Taylor & Francis, 2018)
Cells from patients with acute myeloid leukaemia (AML) that remain dormant and protected by stromal cells may escape effects of chemotherapy. We modelled dormancy in vitro and investigated the ability of Bcl-2 inhibitors ABT-199 and ABT-737 to overcome chemoprotection of dormant cells. CD34-enriched primary AML cells with aberrant leukaemia-associated phenotypes (LAPs) were cultured on stromal cells. The chemosensitivity of dormant (PKH26high), CD34+, LAP+ cells was ascertained by 5-colour flow cytometric counting after 12 days. The PKH26high, CD34+, LAP+ subset retained clonogenic capacity. The dormant fraction was completely resistant to ara-C (P=0.007). However, ABT-199 and ABT-737 were able to reduce the dormant fraction by 84% and 80% respectively of their effects on proliferating counterparts. In conclusion, we have elaborated a system for quantifying chemosensitivity in LAP+ dormant leukaemia cells thought to contribute to disease relapse, and shown sensitivity of dormant LAP+ cells to ABT-199 and ABT-737 in this system.